Adenosine A2A Receptor Blockade Prevents Rotenone-Induced Motor Impairment in a Rat Model of Parkinsonism - Fathalla, Ahmed M.; Soliman, Amira M.; Ali, Mohamed H.; Moustafa, Ahmed A. (Frontiers in Behavioral Neuroscience, 2016)
Pharmacological studies implicate the blockade of adenosine receptorsas an effective strategy for reducing Parkinson's disease (PD) symptoms. The objective of this study is to elucidate the possible protective effects of ZM241385 and 8-cyclopentyl-1,3-dipropylxanthine, two selective A2Aand A1 receptor antagonists, on a rotenone rat model of PD. Rats were split into four groups: vehicle control (1 ml/kg/48 h), rotenone(1.5 mg/kg/48 h, s.c.), ZM241385 (3.3 mg/kg/day, i.p) and 8-cyclopentyl-1,3-dipropylxanthine (5 mg/kg/day, i.p). After that, animals were subjected to behavioral (stride length and grid walking) and biochemical (measuring concentration of dopamine levels using high performance liquid chromatography). In the rotenone group, rats displayed a reduced motor activity and disturbed movement coordination in the behavioral tests and a decreased dopamine concentration as foundby high performance liquid chromatography. The effect of rotenone was partially preventedin the ZM241385 group, but not with 8-cyclopentyl-1,3-dipropylxanthine administration. The administration of ZM241385 has led toan improvement improved of motor function and movement coordination (a partial increase of stride length and partial decrease in the number of foot slips) and an increase in dopamine concentration in the rotenone-injected rats. However, the 8-cyclopentyl-1,3-dipropylxanthine and rotenone groups were not significantly different. These results indicate that selective A2Areceptor blockade by ZM241385, but not A1receptor blockadeby 8-cyclopentyl-1,3-dipropylxanthine, may treat PD motor symptoms. This reinforces the potential use of A2A receptor antagonists as a treatment strategy for PD patients.. This may provide a more selective treatment strategy for PD patients.